Conservation and Divergence of the CONSTANS-Like (COL) Genes Related to Flowering and Circadian Rhythm in Brassica napus - Chen, Yuxi; Zhou, Rijin; Hu, Qiong; Wei, Wenliang; Liu, Jia (Frontiers in Plant Science, 2021)
Abstract The CONSTANS-LIKE (COL) genes are important signaling component in the photoperiod pathway and flowering regulation pathway. However, people still know little about their role in Brassica napus. To achieve a better understanding of the members of the BnaCOL gene family, reveal their evolutionary relationship and related functions involved in photoperiod regulation, we systematically analyzed the BnaCOL family members in B. napus genome. A total of 33 BnaCOL genes distributed unevenly on 16 chromosomes were identified in B. napus and could be classified into three subfamilies. The same subfamilies have relatively conservative gene structures, three-dimensional protein structures, and promoter motifs such as light-responsive cis-elements. The collinearity analysis detected 37 pairs of repetitive genes in B. napus genome. 67.7% of the BnaCOL genes were lost after B. napus genome polyploidization. In addition, the BnaCOL genes showed different tissue-specific expression patterns, and 81.8% of the BnaCOL genes were mainly expressed in leaves, indicating that they may play a conservative role in leaves. Subsequently, we tested the circadian expression profiles of 9 homologous genes that regulate flowering in Arabidopsis. Most BnaCOL genes exhibit several types of circadian rhythms, indicating that these BnaCOL genes are involved in the photoperiod pathway. As such, our research has laid the foundation for understanding the exact role of the BnaCOL family in the growth and development of rapeseed, especially in flowering.